2017
DOI: 10.1021/acs.joc.7b01202
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Iodine(III)-Mediated Decarboxylative Ritter-Type Amination Leading to the Production of α-Tertiary Amine Derivatives

Abstract: α-Tertiary amines (ATAs) are attractive structural motifs that are frequently found in biologically active molecules. Therefore, the development of an efficient method for the synthesis of ATAs represents an important research topic in the field of medicinal chemistry as well as organic chemistry. Although the Ritter reaction is a reliable approach for preparing α-tertiary amine derivatives via intermolecular amination reactions, the typical methods suffer from disadvantages such as harsh reaction conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 62 publications
(38 reference statements)
1
37
0
Order By: Relevance
“…However, despite the great potential of this approach with respect to a decarboxylative C–O bond-forming reaction, the oxidation system was only applied to reactions of uronic acids and α-amino acids [ 22 24 ], and further applications have not been explored. We recently reported on the decarboxylative Ritter-type amination of carboxylic acids containing an α-quaternary carbon center using a combination of PhI(OAc) 2 and I 2 to produce the corresponding α-tertiary amine derivatives ( Scheme 1 ) [ 25 ]. Mechanistic investigations indicated that the reaction proceeds via the formation of an alkyl iodide and the corresponding iodine(III) species as key intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the great potential of this approach with respect to a decarboxylative C–O bond-forming reaction, the oxidation system was only applied to reactions of uronic acids and α-amino acids [ 22 24 ], and further applications have not been explored. We recently reported on the decarboxylative Ritter-type amination of carboxylic acids containing an α-quaternary carbon center using a combination of PhI(OAc) 2 and I 2 to produce the corresponding α-tertiary amine derivatives ( Scheme 1 ) [ 25 ]. Mechanistic investigations indicated that the reaction proceeds via the formation of an alkyl iodide and the corresponding iodine(III) species as key intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…However, with 1 equivalent of CuSO4 the conversion of the product increased to 76% (89% based on the recovered starting material, Table 2, Screening of the reaction conditions and results are presented in Table 2. The first assays for the oxidative decarboxylation were performed on derivative 3a using the pair of oxidizing reagents diacetoxyiodobenzene/iodine (DIB/I 2 ) [25,49]. After several attempts, when a mixture of acetic acid and DCM was used as solvent (Table 2, entry 7) compound 4a was obtained in 59% yield, probably due to the higher solubility of 3a in this solvent mixture.…”
Section: Studies On the Oxidative Decarboxylation Of L-arginine Derivmentioning
confidence: 99%
“…In 2014, Lei reported a photoredox‐catalyzed decarboxylative amination of α‐keto acid . Kiyokawa and Minakata reported Ritter‐type decarboxylative amination with acetonitrile in the presence of PhI(OAc) 2 and I 2 as the oxidants under fluorescent lamp irradiation . Quite recently, Fu, Hu, and MacMillan reported novel copper/photoredox co‐catalyzed decarboxylative aminations of carboxylic acids…”
Section: Figurementioning
confidence: 99%
“…[13] Kiyokawa and Minakata reportedR itter-type decarboxylative aminationw ith acetonitrile in the presence of PhI(OAc) 2 and I 2 as the oxidants under fluorescent lamp irradiation. [14] Quite recently,F u, Hu, and MacMillan reported novel copper/photoredox co-catalyzed decarboxylative aminations of carboxylic acids. [15] During our study on photoredox-catalyzed carbon-nitrogen (CÀN) bond formation, [16] we discovered that our photocatalytic systemsc ould be applicable to the decarboxylative functionalizationo fa rylacetic acids ( Figure 1B).…”
mentioning
confidence: 99%